The women’s empowerment in livestock index - Galiè, Alessandra; Teufel, Nils; Korir, Luke; Baltenweck, Isabelle; Girard, Amy W.; Domínguez Salas, Paula; Yount, K.M. (Springer, 2019)
The empowerment of women in the livestock sector is fundamental to achieve gender equality. It also is instrumental for increased household productivity and improved household health and nutrition. Diverse strategies exist to empower women, yet these strategies are difficult to prioritize without a reliable and adapted means to measure women’s empowerment. One quantitative measure is the Women’s Empowerment in Agriculture Index (WEAI). Despite its reliability in certain agricultural contexts, the WEAI requires adaptation in settings where livestock farming is the dominant form of livelihood. Using the WEAI as a starting point, a multidisciplinary team of researchers developed the Women’s Empowerment in Livestock Index (WELI), a new index to assess the empowerment of women in the livestock sector. This paper presents the WELI and the dimensions of empowerment it includes: (1) decisions about agricultural production; (2) decisions related to nutrition; (3) access to and control over resources; (4) control and use of income; (5) access to and control of opportunities; and (6) workload and control over own time. The paper illustrates the use of the WELI by introducing pilot findings from dairy smallholders in four districts of northern Tanzania. The paper addresses considerations for the appropriate use and adaptation of the WELI to balance the needs for context specificity and cross-cultural comparisons; it also discusses its limitations. The paper recommends participatory and qualitative methods that are complementary to the WELI to provide context-specific insights on the processes of women’s empowerment in the livestock sector.